(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
Gastro-intestinal parasitic infections in dogs represent a major concern in developing countries including Bangladesh. Dogs are important definitive or reservoir hosts for several zoonotic parasites. This study was conducted to determine the prevalence of gastro-intestinal parasites in dogs from different areas of MymensinghSadar. The fecal samples were examined by simple sedimentation and stoll’s ova counting method for detection of eggs/cysts/oocysts of parasites. The overall prevalence of gastrointestinal parasites was 60.00% (51/85) and the mixed parasitic infection was 16.47% (14/85). A total of six species of gastro-intestinal parasites (ova/oocyst) were identified, of them four species were nematode namely,Toxocaracanis (24.7%), Acylostomacaninum (7.05%), Acylostomabraziliense (2.35%), Uncinariastenocephala (2.35%), one species was cestode, Taeniapisiformis (3.52%) and one species was protozoa, Isosporacanis (3.52%). The prevalence of infection was significantly (P<0.02) higher in puppies and young dogs than that in adult dogs. The efficacy of fendnedazole (Bol. Fenvet®), albendazole (Tab. Alben DS®), fenbendazole (Tab. Paraclear®) was 100% effective against single helminth infection. However, the efficacy of mebendazole (Syrup.Mebantrin®) was 25%-50% against mixed helminth infections. The efficacy of metronidazole (Syrup.Amodis®) was 100% against single protozoal infection. So, anthelmintic including albendazole, fenbendazole, mebendazole and metronidazole may be recommended to treat effectively the single infection of helminth and protozoa, respectively, in dogs. Special emphasis should be given to deworm puppies as they are more vulnerable to parasitic diseases. The T. canis, A. caninum, A. braziliense and U. stenocephala prevalent in dogs are zoonotic and have public health impact. Res. Agric., Livest. Fish.7(3): 411-419, December 2020